The European research elite: a cross-national study of highly productive academics in 11 countries - Kwiek, Marek (My University, 2015)
In this paper, we focus on a rare scholarly theme of highly productive academics, statistically confirming their pivotal role in knowledge production across 11 systems studied. The upper 10 % of highly productive academics in 11 European countries studied (N = 17,211) provide on average almost half of all academic knowledge production. In contrast to dominating bibliometric studies of research productivity, we focus on academic attitudes, behaviors, and perceptions as predictors of becoming research top performers across European systems. Our paper provides a (large-scale and cross-country) corroboration of the systematic inequality in knowledge production, for the first time argued for by Lotka (J Wash Acad Sci 16:317–323, 1929) and de Solla Price (Little science, big science. Columbia University Press, New York, 1963). We corroborate the deep academic inequality in science and explore this segment of the academic profession. The European research elite is a highly homogeneous group of academics whose high research performance is driven by structurally similar factors, mostly individual rather than institutional. Highly productive academics are similar from a cross-national perspective, and they substantially differ intra-nationally from their lower-performing colleagues.
Keywords: academic profession; faculty work; faculty research productivity; highly productive academics; higher education policy; European universities; publishing productivity; Lotka's law; Alfred Lotka; Derek de Solla Price; academic stratification; research top performers; highly performing academics; publishing patterns; high publishers; low publishers; academic productivity; research productivity; research hours; teaching hours; teaching and research; predictors of productivity; correlates of productivity; high productivity; European academics; CAP survey; EUROAC survey; Changing Academic Profession; inequality; inequality in knowledge production; knowledge production; European higher education; Social stratification in science; academic inequality; top performers; skewed distribution; refression analysis; highly publishing academics